Pre-Service Teacher’s First-Time Experience in Lesson Planning: Exploring Their Pedagogical Content Knowledge Perspective - Nadia, Hafizhatu (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
This study aims to explore pre-service teachers' first-time experience in lesson planning from their pedagogical and content knowledge perspectives. The study involved four pre-service teachers as participants in a micro-teaching class to answer two theme questions, namely Pedagogic knowledge pre-service students during micro teaching practice and Content knowledge pre-service students during micro teaching practice. This research used interview study as the research design. The data were collected through semi-structured interviews, which were analyzed using thematic analysis. Pre-service teachers shares experiences in implementing their pedagogical and content knowledge into teaching modules in order to create the effective classroom process. Lecturer’s feedback and pre-service teacher reflection after micro teaching practice play a significant role in improving their teaching practices